2007
DOI: 10.1007/s10517-007-0220-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of genetically determined production of immunoregulatory cytokines in immunopathogenesis of chronic viral hepatitides

Abstract: Immunopathogenesis of chronic viral hepatitides was studied by modern immunological, molecular, genetic methods. We revealed an imbalance in the production of immunoregulatory cytokines by mononuclear leukocytes (primarily of the Th2 type). The risk of progression and chronic course of viral hepatitides in Caucasian population was associated with alleles of promoter regions -330G and -592A in the IL-2 and IL-10 genes, respectively, as well as with the T/T genotype of the polymorphic region C590T in the IL-4 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…It has also been reported that the heterozygous C/A variant in the IL-10 gene promoter region C592A is associated with a major risk of progression and chronic course of viral hepatitis in a white population 30. It is therefore likely that an alteration of the host immune system due to genetic predisposition or induced by some proteins of the virus determines the switch in the predominant activation from Th1 to Th2 cells, with a consequent imbalance in the production of immunoregulatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that the heterozygous C/A variant in the IL-10 gene promoter region C592A is associated with a major risk of progression and chronic course of viral hepatitis in a white population 30. It is therefore likely that an alteration of the host immune system due to genetic predisposition or induced by some proteins of the virus determines the switch in the predominant activation from Th1 to Th2 cells, with a consequent imbalance in the production of immunoregulatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…The human IL-4 gene is located on chromosome 5q31 and consists of 25 kbps [16] . So far, more than 50 allelic variant polymorphisms have been found ( http://www.ncbi.nlm.nih.gov/SNP/ ), including −590C/T (rs2243250), −33C/T (rs2070874), +3437C/G (rs2227282), and 2979G/T (rs2227284) [17] . The impact of IL-4 gene polymorphisms in the pathogenesis of HBV infection has been investigated, and numerous studies have suggested that IL-4 variants play pivotal roles in hepatitis B vaccine response and HBV infection risk [18] [21] .…”
Section: Introductionmentioning
confidence: 99%
“…Each study presented the distribution of genotypes in both the cases and controls on independent sampling. Two studies were not consistent with the HWE and were excluded from the meta‐analysis. The included studies had been conducted on a broad range of ethnicities that included participants from Argentina, Brazil, Britain, China, Egypt, India, Italy, Japan, Pakistan, Russia, Tunisia and United States.…”
Section: Resultsmentioning
confidence: 99%